2013
DOI: 10.4236/as.2013.412a003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of controlled-release urea application on the growth, yield and nitrogen recovery efficiency of cotton

Abstract: Field experiments were conducted to study the effects of the controlled release urea (CRU) application on growth yield and nitrogen recovery efficiency of cotton in the main cotton zone of the Yangtze River basin in 2010. Different nitrogen levels were set in order to determine the suitable dosage of CRU on cotton. The special purpose was to provide evidence for the CRU application in cotton fields. The results show that the application of CRU promotes the growth of cotton significantly and enhances the nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This slow release of N corresponded well and might substantially be supported in the fast development of roots and leaves due to more production of chlorophyll content resulting in higher biomass accumulation and ultimately higher plant height and peak LAI (Silvertooth et al 2011 ; Geng et al 2016 ). Moreover, improved plant height and peak LAI might be because of maximum canopy development which resulted in maximum net photosynthetic rate and assimilate portioning and ultimately higher plant height and peak leaf area index (Wang, 2013 ; Tian et al 2017 ). Several studies have reported that plant height and LAI increase with the application of slow-release N fertilizers in cotton production (Li et al 2007 ; Geng et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This slow release of N corresponded well and might substantially be supported in the fast development of roots and leaves due to more production of chlorophyll content resulting in higher biomass accumulation and ultimately higher plant height and peak LAI (Silvertooth et al 2011 ; Geng et al 2016 ). Moreover, improved plant height and peak LAI might be because of maximum canopy development which resulted in maximum net photosynthetic rate and assimilate portioning and ultimately higher plant height and peak leaf area index (Wang, 2013 ; Tian et al 2017 ). Several studies have reported that plant height and LAI increase with the application of slow-release N fertilizers in cotton production (Li et al 2007 ; Geng et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using of CRFs may considerably reduce the energy consumption and time required to grow crops because the nutrients are slowly and gradually released throughout the growing season, hence, only one application is needed. Also consumption of natural gas and waste produced by the fertilizer industry can be reduced because of the more efficient use of nutrients23. However, the use of CRFs is still limited compared with the large amount of more conventional fertilizers applied throughout the world.…”
mentioning
confidence: 99%
“…Recently, considerable research has been devoted to studying the effects of CRUs and CRKs on cotton production. For example, application of CRU has been found to enhance the nitrogen supply throughout the cotton growing season thus promoting crop growth2. CRU application not only increased nitrogen use efficiencies and crop yields but also reduced the labor costs and risks to the environment22.…”
mentioning
confidence: 99%